Resilience and life satisfaction in pregnants, in view of COVID-19, in the multidisciplinary teleservice of Primary Health Care in the SUS (Research, Society and Development, 2022)
Pregnancy is an important moment in the families lifes and, taking into account the psychodynamics of the puerperium, we can consider it as a phase of evolutionary crisis. In Primary Health Care for pregnants, in the SUS, prenatal care starts with the involvement of a multidisciplinary team and comprehensive care, guiding the pregnants and carrying out health promotion. In March 2020, the WHO declared a pandemic state for the new SARS-CoV-2 coronavirus, and in Brazil, pregnants and postpartum up to the 14th day after childbirth were classified in a risk group. In order to optimize health services for the general population and pregnants, it was possible to use remote communication resources. Resilience is a product of individual beliefs that leads to a state of flexibility to face adversity, and consequently, impacts satisfaction with life. The aim of the research was to assess the resilience and satisfaction with life of pregnants in teleservice. This is a longitudinal, exploratory and quantitative research. Fifteen pregnant volunteers were recruited for the study. The instrument used was the Resilience and Satisfaction With Life questionnaires. Although in a short period of application, the multidisciplinary teleservice, during the period of the COVID-19 pandemic, guaranteed good results in terms of resilience and satisfaction with life.